THE ABILITY OF CAVAL/AORTA DIAMETER INDEX TO PREDICT POSTINDUCTION HYPOTENSION (Journal of Pharmaceutical Negative Results, 2023)
Background: We aimed to assess the ability of caval/aorta diameter index in comparison to inferior vena cava (IVC) collapsibility index to predict postinduction hypotension.Methods: This prospective observational study included adult patients undergoing elective non-cardiac surgery under general anesthesia. Before a standardized induction of anesthesia, ultrasonographic measurement of the IVC maximum and minimum diameter and aortic diameter during systole were obtained using M-mode. The IVC collapsibility index and Caval/aorta diameter index were then calculated. The primary outcome was comparison of the ability of the Caval/aorta diameter index and IVC collapsibility index in predicting postinduction hypotension (defined as systolic blood pressure <90 mmHg or >30% reduction from the baseline) using area under receiver operating characteristic curve (AUC) analysis. Results: Ninety-six patients were analyzed from whom 54 (56%) developed postinduction hypotension. The caval/aorta diameter index were lower and the IVC collapsibility index were higher in hypotensive patients in comparison to the non-hypotensive patients. The AUC (95% confidence interval) for the ability to predict postinduction hypotension of caval/aorta diameter index was 0.95 (0.89-0.99) and was comparable to that of the IVC collapsibility index (0.93 [0.87-0.98]). The caval/aorta diameter index showed the highest positive predictive value (98%) at ratio ≤ 0.84.Conclusion: Both caval/aorta diameter index and IVC collapsibility index can accurately predict postinduction hypotension during general anesthesia. The caval/aorta diameter index showed higher specificity than the IVC collapsibility index; at a cut-off value of ≤ 0.84 for the caval/aorta diameter index, the positive predictive value is 98%.